The role of message ambassador elements, music, and color in increasing the persuasiveness of children’s product advertising on YouTube - Dian Marhaeni Kurdaningsih; Didik Murwantono; Anis Turmudhi; Destary Praptawati (EduLite: Journal of English Education, Literature and Culture, 2026)
As digital platforms like YouTube reshape children's product advertising, this study explores how brand ambassadors, music, and color influence consumer engagement and memory. Despite their frequent use, the persuasive roles of these elements remain unclear. Therefore, the aim is to examine how much brand ambassadors, colour, and music in children's product advertisements on YouTube influence parental consumer engagement The research focuses on their impacts on recall and brand reinforcement among parents. This study was under a quantitative research. It was designed to quantitatively examine the impact, employing a survey as the primary research method.  An online survey was conducted with 100 parents of children aged 5 to 10. A total of 20 advertising videos were collected and subsequently examined through regression analysis. The results of the correlation analysis revealed that brand ambassadors significantly and positively enhance the persuasive power of advertisements for children's products. Likewise, the use of color demonstrated a substantial and statistically significant effect. In contrast, music exhibited a relatively strong influence but did not reach statistical significance. Foundational attributes, such as credibility, popularity, and appeal in brand ambassadors, as well as memorability and attractiveness in musical elements, consistently contributed to increased consumer persuasion through brand reinforcement and recall, particularly when paired with color. These findings offer valuable, data-driven insights for advertisers, policymakers, and scholars seeking to optimize audiovisual strategies in digital campaigns targeting children's markets. However, a key limitation of this study lies in the absence of mediating variables, which could have provided a deeper understanding of the mechanisms behind persuasion. Future research is encouraged to incorporate such variables further and investigate additional advertising components that may influence consumer response.